Plat-Forms Is there one best Web development technology? - PRECHELT, LUTZ (Communications of the ACM, 2010)
The article presents information on the results of a contest in which teams of software programmers attempted to create a web-based system in 30 hours, using a computer program language platform such as Java, Perl or PHP. Their results were then evaluated in terms such as functionality, source code size, security and robustness. Information on the relative performance of the teams and platforms is presented, and some of the strengths and weaknesses of each programming platform language are analyzed.